Dermoscopic patterns in patients with a clinical diagnosis of onychomycosis-results of a prospective study including data of potassium hydroxide (KOH) and culture examination - Miriam América Jesús-Silva; Ramón Fernández-Martínez; Rodrigo Roldán-Marín; Roberto Arenas (Mattioli1885, 2015)
Background: Onychomycosis is the most common nail disease, representing 50% of cases affecting the nail apparatus. The diagnosis is made by clinical examination along with the KOH exam of the nail and culture of the sample. However, not all dermatologists have access to a mycology lab. Objective: To determine the correlation between KOH examination and dermoscopic patterns in patients with clinical diagnosis of onychomycosis. Patients/Methods: A descriptive, open, observational, prospective, cross-sectional study of 178 patients with clinical suspicion of onychomycosis was conducted. All patients underwent clinical examination, dermoscopy with a DermLite PHOTO dermatoscope (3Gen, San Juan Capistrano, CA, USA), KOH assessment and culture analysis. The most frequent dermoscopic patterns were identified and their correlation with the clinical subtype of onychomycosis was analyzed. Results: The study included 178 patients with clinical suspicion of onychomycosis. Of these, 155 (87.1%) had positive direct KOH examination for onychomycosis. Eighty-seven patients (56.13%) presented with clinical onychomycosis pattern of total dystrophic onychomycosis (TDO), 67 (43.23%) with distal lateral subungual onychomycosis (DLSO), 1 (0.65%) with trachyonychia). Dermoscopic patterns of onychomycosis showed the following frequencies: the spiked pattern was present in 22 patients (14.19%), longitudinal striae pattern in 51 patients (32.9%) and linear edge pattern in 21 patients (13.55%). We identified a pattern described as "distal irregular termination" in 41 patients with TDO and 26 with DLSO. Conclusions: This is the fist study conducted in a Mexican population that uses dermoscopy as a diagnostic tool along with the KOH examination for the diagnosis of onychomycosis. Dermoscopy may be used as an important diagnostic tool when evaluating nail disease. However, it should not be used as the only diagnostic criteria for onychomycosis.